2008
DOI: 10.1590/s0006-87052008000400026
|View full text |Cite
|
Sign up to set email alerts
|

Danos de frio e alterações qualitativas durante armazenagem refrigerada de pêssegos colhidos em dois estádios de maturação

Abstract: RESUMOPêssegos 'Chimarrita' e 'Chiripá' foram colhidos nas safras de 2000 e 2001, nos estádios de maturação de vez e maduro e armazenados a 0 ºC e 90% de umidade relativa. Os pêssegos 'Chiripá' permaneceram armazenados sob refrigeração por 10 ou 20 dias em 2000 e por 7, 14 ou 21 dias em 2001, enquanto os pêssegos 'Chimarrita' foram conservados em câmara frigorífica nas duas safras por 10, 20 ou 30 dias. Amostras de pêssegos foram avaliadas na colheita, em cada saída de armazenagem refrigerada e após 2 ou 3 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…At the end of 30 days, TA content reduction reached 20% compared to the initial value. Similar behavior was observed by Seibert et al (2008). According to Chitarra & Chitarra (2005), TA reduces ripening evolution.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…At the end of 30 days, TA content reduction reached 20% compared to the initial value. Similar behavior was observed by Seibert et al (2008). According to Chitarra & Chitarra (2005), TA reduces ripening evolution.…”
Section: Resultssupporting
confidence: 79%
“…Seibert et al (2008) observed similar behavior in 'Chimarrita' peaches under refrigeration at 0 °C and 90% RH. SS concentration increases during cold storage due to fruit weight loss by transpiration (Pinto et al, 2012).…”
Section: Resultssupporting
confidence: 61%
“…Despite displaying more than 5% loss, the fruits showed no symptoms of shriveling, which would prevent its commercialization. Seibert et al (2008) observed that peaches cv. Chimarrita after 10 and 30 days of refrigerated storage, when brought to 20 °C, showed slight wilting in the shoulder region.…”
Section: Resultsmentioning
confidence: 99%
“…For Crisosto et al (2004), mass losses of 5% are normal for peaches and shriveling symptoms are noticed when they exceed 10%. For the cultivars Chimarrita and Chiripá, a loss limit of 5% and higher percentages can lead to symptoms of shriveling (Seibert et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation